Why is Math Difficult? : Beliefs That Affecting Students' Mathematics Skills - Purbaningrum, Mayang; Ramadhan, Sahrul; Thauzahra, Raudya (Universitas Pendidikan Mandalika, 2023)
This research aims to describe the factors that influence students' beliefs that mathematics is difficult and how to change students' beliefs that mathematics is not difficult. This research method used a Systematic Literature Review with a qualitative approach. This data was obtained from the thematic analysis of several books and articles discussing 'intelligence